Energy transfer studies of Dy3+ ions doped K2GdF5 crystal - Tuyen, Vu Phi; Do, Phan Van; Khaidukov, N.M.; Thanh, Nguyen Trong (VNU Journal of Science: Mathematics - Physics; Vol 28 No 2, 2012)
Abstract. Dy 3+ -doped K 2 GdF 5 single crystals were synthesized under hydrothermal condition. The UV excitation spectra and lifetimes of K 2 GdF 5 :Dy 3+ were measured at room temperature. The excitation spectra have shown charge transfer state (CTS) of Dy 3+ and energy transfer from Gd 3+ to Dy 3+ ions in K 2 GdF 5 :Dy 3+ crystal. The decay curve of the K 2 GdF 5 sample doped with 5.0 mol % Dy 3+ ions is a non – exponential curve and is well fitted to the Inokuti – Hirayama model for S = 6. The energy transfer parameters ( Q , C DA ) and the critical distance ( R 0 ) are calculated. Keywords: K 2 GdF 5 single crystal, Inokuti – Hirayama model.